SMMEs and Financial Reporting: Information Technology as Tool to Enhance Performance and Economic Progression in Durban Municipality, KwaZulu-Natal - Sinenhlanhla T.N. Khumalo; L.M. Lekhanya (Economics and Entrepreneurship: The Proceedings of the 10\(^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
Background: SMMEs drive South Africa’s economic growth, employment generation, and poverty reduction. During the 1990s, South Africa passed the National Small Business Act and established SEDA to encourage SMMEs’ sustainability and ease the regulatory burden. The National Development Plan targets SMMEs to create 90% of new South African jobs by 2030. SMMEs are vital to the economy but fail to sustain themselves. 60–80% of SMMEs fail within the first three years. Lack of strategic resource usage, managerial skills, financial report creation, and regulatory awareness and compliance contribute to the high failure rate. Research Method: Quantitative methodology was deployed in the collection, analysis and presentation of data collected from 248 SMMEs, forming the sample size. Derived from the population of 700 SMMEs within the Durban Municipality, through non-purposive convenience sampling, according to the willingness and availability to participate in the study. Data was collected via a Likert questionnaire and subsequently analysed using SPSS 29.0. Findings: Findings, through Spearman’s correlation values; crosstabulation and descriptive data collected and analysed indicate that SMMEs’ struggle with failure to produce regulatory-compliant financial reporting and their inability to strategically use information technology contributes to their challenge to sustain themselves. Furthermore, compliance cost is also a difficulty SMMEs face. Conclusion: Information technology may aid SMMEs in preparing regulatory-compliant financial reports, improving their economic growth and sustainability. Given the challenges SMMEs face, the government should empower them to use information technology strategically to minimise compliance, cost, and risks in producing accurate financial reports, maximising sustainability and economic growth.